Polypyrrole nanotubes: The tuning of morphology and conductivity. (24th March 2017) - Sapurina, Irina; Li, Yu; Alekseeva, Elizaveta; Bober, Patrycja; Trchová, Miroslava; Morávková, Zuzana; Stejskal, Jaroslav
Abstract: Polypyrrole nanotubes rank among important functional materials with high application potential. They are prepared by the oxidative polymerization of pyrrole usually in the presence of methyl orange and represent conducting polymers with the highest bulk conductivity, 40–50 S cm −1 . The role of methyl orange in promoting the nanotubular morphology of polypyrrole is discussed on the basis of FTIR and Raman spectra. The model based on the organization of acid form of methyl orange molecules to an in-situ -generated solid template is proposed. Various factors controlling the morphology and conductivity of polypyrrole have been identified. Higher acidity of reaction medium or the addition of ethylene glycol increased the diameter of nanotubes or even converted nanotubes to globules, and the conductivity was reduced. Nanotubes have not been obtained at temperature elevated to 60 °C but one-dimensional polypyrrole morphology was surprisingly produced even when the oxidation of pyrrole took place in frozen reaction medium, in ice, at −24 °C. The counter-ions in iron(III) salt used for the oxidation and the presence of water-soluble polymers had virtually no influence on morphology and conductivity. On the other hand, a series of organic dyes used as replacement of methyl orange had substantial effect on both the nanotubular morphology and conductivity. The role of template formation is discussed by comparing methyl orange and ethyl orange dyes. While the former dye precipitates under acidic conditions and supports the growth of nanotubes, the latter does not and globules are obtained instead. Graphical abstract: Highlights: Polypyrrole nanotubes rank among the most conducting polymer materials. The formation and the role of the templates in the growth of nanotubes is discussed. The acidity of reaction medium strongly affects the conductivity of nanotubes. The nanotubes were produced even in the frozen reaction medium. Methyl orange support the formation of nanotubes, ethyl orange does not.